Laser Processing of Reflective Materials. Issue 1 (14th January 2013) - Naeem, Mohammed
Abstract The favourable strength to density ratio of metals and alloys, as well as their good formability and weld‐ability characteristics, are some of the reasons why they account for over half the materials in industrial applications. The most common groups of engineering metals and alloys are steels, titanium alloys, nickel alloys and reflective materials such as aluminium, copper, silver and gold. Compared to traditional techniques, lasers offer manufacturers a highly accurate, easily repeatable, automated and non‐contact means of processing these materials. Their use helps drive down costs and drive up manufacturing quality by reducing tool wear, eliminating the need for additional finishing, improving overall product quality and maximising material usage.